ANALISIS PENGELOLAAN DAN PERTANGGUNGJAWABAN PENGGUNAAN DANA DESA - Bambang Widarno, Pujiyanti, Suharno & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to know the management and accountability of the use of funds of the village in the village of Blora Regency Kecamatan Randublatung, as well as the factors that support and hinder the provision of management and accountability the use of the village fund. This research is a case study in the village of Blora Regency Kecamatan Randublatung, types of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this research is the entire village of devices involved in the management of the village Fund, that as many as 30 people. The number of samples in the study as many as 30 people, so this research is the study of the census. Data collection techniques using questionnaires, observation and documentation. Data analysis techniques using qualitative deskiptif analysis. The research results obtained the conclusion that: the use of the village Fund in terms of planning and budgeting, execution, administering and reporting and accountability of entry categories. Restricting factors in the management of and accountability for the use of funds of the village, namely in the form of the limited human resources and funding the village obtained the village does not comply with budget planning, while the supporting factors in the management and accountability for the use of the village Fund, namely government support as well as village community participation in supporting the development of the village.Keywords: management and accountability, the village fund